The poorcraft cookbook - O'Reilly, Nero Villagallos; Spike, 1978- (Iron Circus Comics, 2022)
The Poorcraft series is the essential comic book guide to practical urban and suburban frugality! We've shown you how to live better, travel better, and now? Get ready to learn how to eat better on the cheap with The poorcraft cookbook, a comprehensive guide featuring recipes from around the world, vegetarian and vegan meals, food shopping guides, equipment ideas -- even a few cocktail mixers! Whether you're new to independent living, a recent college graduate, or just downshifting to a simpler lifestyle, Poorcraft comics can help you with everything from finding a home to finding a hobby, dinner to debt relief, education to entertainment.